Turbulence in Crit Assessment: from the Design Workshop to Online Learning - Tessier, Virginie; Aubry-Boyer, Marie-Pier (Design and Technology Education: An International Journal, 2021)
Critique in design education is redefining itself, but its primary aim still focuses on offering and receiving feedback on workshop projects. The global pandemic has forced teachers to adapt their methods for online workshops. The following paper questions how design critique has changed teaching and learning experiences, focusing on the distinctions between in-person and online sessions. Before winter 2020, students used to wander through the school’s workshops, filled with sketches and models of ongoing projects. Since then, we were faced with the loss of a shared physical space leading to many changes that should be addressed as online workshops are going forward. As a result, the pandemic has accentuated some of the challenges of offering detailed feedback to projects and has shown the complexity to stimulate students’ interactions during a critique. Gaps created through social distancing seem to have impacted not only the critique activity but the entire project and learning process. By exploring the teaching experiences of a dozen workshop tutors, this paper brings out concerns about the metamorphosis of general interactions and highlights an impact on the design activities. By referring to Lave and Wenger’s situated learning, we discuss the importance of interactions while conducting projects by explaining, discussing, showing, or just looking at what others have done. This paper provides an overview of key elements to improve feedback and communication, emphasising that constant interactions with peers, teachers, and experts are especially meaningful to prepare the designer to its future community of practice.